A prospective analytical study of intrauterine fetal death cases and associated maternal condition at a tertiary centre - Gehlot, Hanslata; Nagar, Girdhar Gopal; Sharma, Seema; Yadav, Om Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine fetal death (IUFD) is a cataclysmic event for the parents and a lamentable event for the caregiver. Intrauterine fetal death is an important indicator of maternal and perinatal health of a given population. This study was undertaken to study the maternal and fetal factors associated with intrauterine fetal death. In this traumatic time, it is important to ensure that the emotional needs of the family are met. The objective of the study was to evaluate and understand the prevalence, socio-epidemiological and etiological factors of IUFD. Methods: This was a prospective analytical study carried out at Umaid Hospital associated to Dr. S. N. Medical College, Jodhpur, Rajasthan from August 2015 to Jan 2016 for a duration of 6 months. Informed consent was taken from all the participants. A predesigned proforma was used to collect relevant information from all those who gave consent to participate in the study. The details of complaints at admission, obstetrical history, menstrual history, examination findings, per vaginal examination findings, mode and method of delivery, and fetal outcome and investigation reports were recorded. Results: A total of 435 intrauterine fetal deaths were reported amongst 11615 deliveries conducted during the study period in our hospital. The incidence of IUFD was 37/1000 live births. 327 (75.17%) deliveries were unbooked and unsupervised and had no antenatal check-up. 306(70.74%) patients were from rural areas and 243 (50.11%) were preterm and 430(98.85%) were singleton delivery. Amongst the identifiable causes, hypertensive disorders (22.75%) and very severe anaemia (13.10%) were the most common ones followed by placental causes (9.97%). Congenital malformations were responsible for 11.03% cases of IUFD and in rest 10.57% cases no obvious cause could be identified. Induction was done in 195 patients, 174 patients had spontaneous onset of labour and caesarean section was done in 66 patients. Conclusions: The incidence of intrauterine fetal deaths in our population is higher than that reported from the developed countries. The present study is an effort to compile a profile of maternal, fetal and placental causes culminating in IUFD at our centre. This emphasizes the importance of proper antenatal care and identification of risk factors and its treatment. Institutional deliveries should be promoted to prevent IUFD. Decrease in the incidence of IUFD would significantly reduce the perinatal mortality. Majority of fetal wastage can be prevented with universal and improved antenatal care.